Li3Ge3Se6: the first ternary lithium germanium selenide with interesting ∞[Ge6Se12]n chains constructed by ethane-like [Ge2Se6]6− clusters. Issue 47 (14th November 2017) - Li, Guangmao; Zhen, Ni; Chu, Yu; Zhou, Zhongxiang
Abstract : The first lithium germanium selenide, Li3 Ge3 Se6 with the first discovered chain formed by [Ge2 Se6 ] 6− clusters in the [Li3 Se6 ] tunnels. Abstract : Li3 Ge3 Se6, the first compound of the ternary Li/Ge/Se system, has been synthesized. Note that interesting 1D∞ [Ge6 Se12 ] n chains constructed by ethane-like [Ge2 Se6 ] 6− clusters were discovered in its structure. Investigations on the structures of all the [Ge2 Se6 ] 6− cluster-containing compounds have shown that only in Li3 Ge3 Se6 are there 1D chains composed of [Ge2 Se6 ] 6− clusters, which result from the space limitation within the tunnels surrounded by LiSe6 octahedra. Raman spectrum was obtained to demonstrate the existence of Ge–Ge bonds. UV-visible-NIR diffuse reflection spectrum showed an optical bandgap of 2.08 eV. Theoretical calculations based on first principles have also been performed for its band structure and density of states to analyze its structure–property relationship.